Evaluation on hypoglycaemic properties of aqueous ettingera elatior flower extract on diabetic-induced rats: a pilot study - Hui, Lim Bee (2020)
Diabetes mellitus (DM) is a metabolic disorder characterised by persistent hyperglycaemia, in which an excessive amount of glucose circulates in the blood. In Malaysia, Etlingera elatior has been used traditionally for reducing blood glucose levels. This pilot study was designed to evaluate the hypoglycaemic properties of aqueous E. elatior flower extract (AEEFE) on a self-made high-fat diet (HFD) and streptozotocin (STZ)-induced diabetic Sprague Dawley (SD) rats. There were 2 phases in the pilot study: induction of obesity (prediabetic state) using self-made HFD and induction of Type 2 diabetes mellitus (T2DM) using 30 mg/kg STZ. Due to the Movement Control Order (MCO) imposed by the Malaysian government because of the pandemic Covid-19 outbreak, only the results from the first part of the study had been analysed. The Body Mass Index (BMI) of the Sprague Dawley (SD) rats reached the obesity category after 4 weeks of HFD feeding despite there was a reduction of food intake. The blood glucose level and systolic blood pressure (SBP) of the experimental group were also increased. Although the second phase of the study cannot be continued due to MCO, the expected results were still being reported based on the data and information from the previously published articles. The effects of AEEFE in the biochemical and histopathological examinations were expected to exhibit improved results when compared to the untreated diabetic group. The bioactive compounds present in the AEEFE such as anthocyanin and flavonoid were expected to minimise the complications from hyperglycaemia and increase insulin sensitivity. Therefore, from all the evidence collected in the expected effects on AEEFE, E. elatior flower is expected to have hypoglycaemic potential in treating T2DM.